The Effect of Psychological Empowerment and Proactive Behavior on Workforce Agility - Ade Purnamasari; Wustari L. Mangundjaya (Green Publisher, 2024)
One of the challenges faced by the manufacturing industry is to increase the level of change in order to remain competitive in the market. Organizations must be able to respond to dynamic changes, a competitive environment in order to continue to survive and develop better. Workforce agility is viewed as a means for firms to survive and flourish effectively in the face of difficulties and competition. In this study, A theoretical model examining the impact of psychological empowerment and proactive behavior on workforce agility was developed and empirically tested. Multiple linear regression revealed that psychological empowerment and proactive behavior were favorably and substantially associated to workforce agility. The results also demonstrated that psychological empowerment has a greater influence than proactive behavior in explaining workforce agility.